Regards croisés de l’économie sur les services écosystémiques et environnementaux - Géraldine Froger; Philippe Méral; Jean-Francois Le Coq; Olivier Aznar; Valérie Boisvert; Armelle Caron; Martine Antona (VertigO)
Since the mid-1990s, the concept of ecosystem services has been growing in popularity at academic and operational level. The aim of this paper is to analyse the different meanings of these concepts in economic science. In this context, it is important to explain the origin of the notion of ecosystem services in order to put forward a typology that treats them as externalities, or as provision of services, or as services included in a product subject to a market transaction. On the basis of our typology, we develop a critical analysis on various regulating instruments for these services.